The HIV care cascade for older adults in rural South Africa: a longitudinal cohort study (2014-2019) - Rohr, Julia K.; Manne-Goehler, Jennifer; Gómez-Olivé, F. Xavier; Kahn, Kathleen; Bärnighausen, Till (Journal of acquired immune deficiency syndromes, 2024)
BACKGROUND: As people with HIV grow older, stable engagement in care is essential for healthy aging. We evaluate the HIV care cascade for older adults in rural South Africa at 2 time points cross-sectionally and assess movement in the cascade over time. - SETTING: We evaluated the cascade stage at waves 1 (2014-2015) and 2 (2018-2019) of Health and Aging in Africa: A Longitudinal Study of an INDPETH Community in South Africa, a population-based longitudinal cohort study in Mpumalanga Province, South Africa. - METHODS: Biomarker screening defined cascade stages [HIV+/no antiretroviral therapy (ART); ART+/unsuppressed viral load; ART+/suppressed viral load]. Between-wave probability of death, cascade progression, regression, cascade transitions, and sociodemographic predictors were assessed with Poisson regression. The impact of death was considered using the Fine and Gray competing risk model. - RESULTS: We observed a higher prevalence of antiretroviral therapy with viral suppression over time (50% in wave 1 vs. 70% in wave 2). Among those alive, the oldest age group (70+ years old) was most likely to have cascade progression [adjusted risk ratio for treatment initiation vs. 40-49 years old: 1.38 (95% confidence interval: 1.02 to 1.86)]. However, there was a significant risk of death and cascade regression. Death between waves reached 40% for 70+-year-olds who were ART+/unsuppressed. In competing risk models, older age was associated with equivalent or less cascade progression. - CONCLUSION: Older age groups who were unsuppressed on treatment and men had poorer cascade outcomes. Improvements observed in HIV treatment coverage over time for older adults must be interpreted in the context of the high risk of death for older HIV-positive adults, especially among those failing treatment.
Gesehen am 29.01.2025